Erratum to: "Comments on the article: O. M. Povoroznyk, O. K. Gorpinich. Experimental observation of neutron-neutron correlations in nucleus 6He from 3H(α, pα)nn reaction" - B. G. Struzhko (Ядерна фізика та енергетика)
Original article: Yaderna Fizyka ta Energetyka (Nucl. Phys. At. Energy) 22(1) (2021) 111.